2007
DOI: 10.1086/521200
|View full text |Cite
|
Sign up to set email alerts
|

Allele-Specific Targeting of microRNAs to HLA-G and Risk of Asthma

Abstract: HLA-G is a nonclassic, class I HLA molecule that has important immunomodulatory properties. Previously, we identified HLA-G as an asthma-susceptibility gene and discovered that the risk of asthma in a child was determined by both the child's HLA-G genotype and the mother's affection status. Here we report a SNP in the 3' untranslated region of HLA-G that influences the targeting of three microRNAs (miRNAs) to this gene, and we suggest that allele-specific targeting of these miRNAs accounts, at least in part, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
273
5
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(296 citation statements)
references
References 34 publications
12
273
5
6
Order By: Relevance
“…In our case-control study, we identified a strong association (P=0.0004) between rs12731181 and essential by guest on May 11, 2018 http://atvb.ahajournals.org/ Downloaded from hypertension in the Han Chinese population in both men and women. Moreover, carriers with the risk G allele exhibited elevated expression of FP in peripheral tissues and had significantly higher SBP and DBP than individuals with the AA genotype.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In our case-control study, we identified a strong association (P=0.0004) between rs12731181 and essential by guest on May 11, 2018 http://atvb.ahajournals.org/ Downloaded from hypertension in the Han Chinese population in both men and women. Moreover, carriers with the risk G allele exhibited elevated expression of FP in peripheral tissues and had significantly higher SBP and DBP than individuals with the AA genotype.…”
Section: Discussionmentioning
confidence: 72%
“…12 SNPs in miRNA-target sites in the 3′UTR of genes represent a specific class of functional polymorphisms and may lead to the dysregulation of post-transcriptional gene expression by disrupting regulatory miRNA binding. 13 An increasing number of 3′UTR SNPs in miRNA binding sites have been found to be associated with a variety of complex human diseases, such as hypertension, 14 cancer, 15 Tourette syndrome, 16 asthma, 17 and Parkinson disease. 18 Recently, a European genome-wide association study reported that the SNP rs12731181, located in the FP 3′UTR, may be associated with increased risk for hypertension in individuals from southern Germany (P=2.5×10 -4 ), but this association was not replicated in other European populations.…”
mentioning
confidence: 99%
“…MiRNAs are involved in diverse biological processes, including development, stress response, cancer, and cardiac hypertrophy, implicating them in normal and pathological processes (8). However, to the best of our knowledge, studies relevant to asthma or asthma risk are still lacking, except for a recent report demonstrating that a single nucleotide polymorphism at the 3' untranslated region of HLA-G, an asthma-susceptibility gene, affects the binding of three miRNAs to this gene (9). Allergic airway inflammation may be particularly sensitive to miRNA regulation since it is characterized by marked changes in gene and protein expression in the lung (1012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, at the 3'-UTR, a 14-bp ins/del has been widely reported as causing mRNA instability (rs371194629) (Rousseau et al, 2003). The presence of a G allele at rs1063320 (3142C>G) is known to increase the site affinity for microRNA, favoring mRNA degradation (Tan et al, 2007). Being upstream of an AU-rich motif involved in mRNA degradation, the A allele at rs9380142 (3187A>G) decreases HLA-G expression (Yie et al, 2008).…”
Section: Introductionmentioning
confidence: 99%